If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(n + -4) = 40 + -4n Reorder the terms: -6(-4 + n) = 40 + -4n (-4 * -6 + n * -6) = 40 + -4n (24 + -6n) = 40 + -4n Solving 24 + -6n = 40 + -4n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '4n' to each side of the equation. 24 + -6n + 4n = 40 + -4n + 4n Combine like terms: -6n + 4n = -2n 24 + -2n = 40 + -4n + 4n Combine like terms: -4n + 4n = 0 24 + -2n = 40 + 0 24 + -2n = 40 Add '-24' to each side of the equation. 24 + -24 + -2n = 40 + -24 Combine like terms: 24 + -24 = 0 0 + -2n = 40 + -24 -2n = 40 + -24 Combine like terms: 40 + -24 = 16 -2n = 16 Divide each side by '-2'. n = -8 Simplifying n = -8
| 14(y-3)=10(5+y) | | 3(3x+4)-3=66 | | 3(3+4x)-3=66 | | x^2+37x+36= | | 7x-6x=70 | | 8x-(6x+6)=2 | | 10-(2x-5)=3(4x-2)-(5x-8) | | -3(x+1)+4x=10 | | x/3+26=25 | | 8x-(3x+4)=12 | | 3x^2-26x=-2x-7x-12 | | 4t-t-8=2t-4 | | 42=-5x+2 | | 6k+k+4=25 | | 4(6t+2)=80 | | 4(6t+2)=55 | | -31-4x=-5-(1+5x) | | (4a-3b+c-5d)5= | | 4(6t+2)=54 | | 4x+x-5=4x+4 | | 4(6t+2)=52 | | -2(21y)= | | 4(6t+2)=53 | | 4(6t+2)=60 | | -2x=-2+8 | | 5x-6=-81 | | 4(6t+2)=4 | | 5x+12-9x=19-15x+11x-7 | | 7x-6x+4x-9x= | | 9+8q=11+7q | | 4(6t+2)=50 | | 4(6t+2)=40 |